A Simplified Risk-Ranking System for Prioritizing Toxic Pollution Sites in Low- and Middle-Income Countries - Jack Caravanos (Ubiquity Press, 2014)
Background: In low- and middle-income countries (LMICs), chemical exposures in the environment due to hazardous waste sites and toxic pollutants are typically poorly documented and their health impacts insufficiently quantified. Furthermore, there often is only limited understanding of the health and environmental consequences of point source pollution problems, and little consensus on how to assess and rank them. The contributions of toxic environmental exposures to the global burden of disease are not well characterized. Objectives: The aim of this study was to describe the simple but effective approach taken by Blacksmith Institute’s Toxic Sites Identification Program to quantify and rank toxic exposures in LMICs. This system is already in use at more than 3000 sites in 48 countries such as India, Indonesia, China, Ghana, Kenya, Tanzania, Peru, Bolivia, Argentina, Uruguay, Armenia, Azerbaijan, and Ukraine. Methods: A hazard ranking system formula, the Blacksmith Index (BI), takes into account important factors such as the scale of the pollution source, the size of the population possibly affected, and the exposure pathways, and is designed for use reliably in low-resource settings by local personnel provided with limited training. Findings: Four representative case studies are presented, with varying locations, populations, pollutants, and exposure pathways. The BI was successfully applied to assess the extent and severity of environmental pollution problems at these sites. Conclusions: The BI is a risk-ranking tool that provides direct and straightforward characterization, quantification, and prioritization of toxic pollution sites in settings where time, money, or resources are limited. It will be an important and useful tool for addressing toxic pollution problems in LMICs. Although the BI does not have the sophistication of the US Environmental Protection Agency’s Hazard Ranking System, the case studies presented here document the effectiveness of the BI in the field, especially in low-resource settings. Understanding of the risks posed by toxic pollution sites helps assure better use of resources to manage sites and mitigate risks to public health. Quantification of these hazards is an important input to assessments of the global burden of disease.